Evaluation of the Al-Qur’an Education Park Program Using the CIPP (Context, Input, Process, and Product) Model - Zainuddin, Zainul Tria Putra; Hamdany, M. Zuljalal Al; Wulandari, Dinda (Educational Journal of Learning Technology, 2025)
This study evaluates the Al-Qashash Qur’anic Education Park program using the CIPP (Context, Input, Process, Product) model. Data were collected through observation, interviews, and documentation, then analyzed qualitatively. The results show that learning objectives are only clear for early levels, while advanced levels lack measurable goals. The institution has a vision but no supporting mission. Teachers lack formal training, and facilities are limited. The learning process includes lectures, Q&A, practice, and assignments, but still requires improvement. This evaluation highlights areas needing development to enhance the program’s effectiveness.